Bioterrorism: A contexture in Indian perspective - RANA, N (The Indian Journal of Animal Sciences, 2018)
The threat of biological warfare has been engaging the attention of Indian defence and medical experts for a long time indicating the vulnerability of the country to a potential public health threat. This paper gives an overview of bioterrorism; its historical facets, attributes of bioterrorism agents and impact of advancement in biotechnology on development of biowarfare agents. Effective bioterrorism planning, prevention and response requires cooperation and collaboration between law enforcement and public health. The paper discusses the biodefence preparedness and constraints from the Indian standpoint and identifies the need for a definitive constitutional framework to put into place a robust legislative mechanism to check the growing threat of biological warfare. Keeping in view the expertise of veterinarian in education and surveillance of zoonotic diseases, their integration in the public health disease surveillance and reporting system and participation in the fight against bioterrorism is imperative.